[Afisz. Incipit] Ochotnicza Straż Pożarna w Pelplinie obchodzi w dniu 22. września 1946 r. pod protektor. J. E. X. Biskupa Dr. Kowalskiego Jubileusz 55-lecia 1891-1946 ... ([wydawca nieznany], 1946)
Afisz z programem obchodów.